CURRENT STATE AND DEVELOPMENT PROSPECTS OF TRAINING INFORMATICS TEACHERS IN GENERAL EDUCATION SCHOOLS - Zilola Botirovna Karimova (Innovate Conferences, 2026)
This article analyzes the current state of training computer science teachers for general education schools, identifies existing problems, and outlines future development prospects. In the context of digitalization of the education system in Uzbekistan, the professional competencies of computer science teachers, their level of proficiency in modern information technologies, and their pedagogical preparedness are becoming increasingly important. The study provides recommendations for improving the balance between theory and practice in teacher training, developing digital competencies, and enhancing the professional development system for computer science teachers.
Keywords: computer science teacher, general education school, digital competence, pedagogical preparedness, professional development.